Randomized clinical trial of peer integrated collaborative care intervention after physical injury - Eileen M Bulger; Peter Thomas; Jin Wang; Lauren K Whiteside; Ronald Maier; Allison Engstrom; Douglas F Zatzick; Joan Russo; Patrick Heagerty; Khadija Abu; Tanya Knutzen; Jake Shoyer; et al. (Trauma Surgery & Acute Care Open)
Objectives The goal of the current study was to assess the effectiveness of a peer integrated collaborative care intervention for postinjury outcomes.Methods Injury survivors ≥18 years of age were screened for post-traumatic stress disorder (PTSD) symptoms and severe postinjury concerns; screen-positive patients were randomized to the intervention versus enhanced usual care control conditions. The collaborative care intervention included peer support and care management. The intervention also included evidence-based pharmacotherapy and psychotherapeutic elements targeting PTSD. The COVID-19 pandemic interrupted recruitment between March and June 2020; in response to the COVID-19 pandemic, the peer component of the intervention went from in-person to virtual delivery. The primary outcomes were PTSD symptoms assessed with the Diagnostic and Statistical Manual of Mental Disorders fourth edition PTSD checklist, any severe postinjury concerns, and emergency department/inpatient utilization followed over the 12 months postinjury. Secondary outcomes included patient satisfaction with emotional healthcare.Results A total of 450 patients were randomized to the intervention (n=225) and control (n=225) conditions; 124 patients (28%) were recruited and completed all study assessments prior to the onset of the COVID-19 pandemic, while 326 patients (72%) were recruited after and/or had one or more study follow-ups occur postpandemic onset. Mixed model regression revealed no statistically significant comparisons for any of the primary outcomes. In exploratory models that examined the impact of COVID-19, significantly improved PTSD symptoms were present at 3 months pre-COVID-19 relative to post-COVID-19. Intervention patients consistently demonstrated higher satisfaction with emotional aspects of healthcare (F(5,1652)=2.87, p=0.01).Conclusions The intervention demonstrated no significant improvements in primary outcomes in the intent-to-treat sample. The peer integrated collaborative care intervention contributed to higher patient satisfaction with the emotional aspects of healthcare.Level of evidence Level II, randomized clinical trial.Trial registration number NCT03569878.